Ação antioxidante de derivados do líquido da castanha de cajú (LCC) sobre a degradação termooxidativa do POLI (1,4-CIS-ISOPRENO) - Rodrigues, Francisco Helder Almeida (2006)
Cashew nut shell liquid (CNSL) is a mixture of meta-alkyl-phenols which varies on its degree of unsaturation attached to the benzene nucleus. The kinetic study of the thermal degradation at 140°C of synthetic cis-1,4-polyisoprene film, in the absence and presence of technical and natural CNSL and some derivatives (anacardic acid, cardol, cardanol, hydrogenated cardanol and alkylated hydrogenated cardanol) was carried out by infrared spectroscopy through the evolution of the relative absorbance of the bands in 3450 cm-1, 1720 cm-1 and 835 cm-1. The amount of hydroxyl and carbonyl group formed and also of carbon double bond consumed during the degradation was determined. All material studied showed antioxidant activity that was verified by an increase in the induction period and a decrease in the apparent rate constants of thermal-oxidation. The antioxidant effectiveness is higher for the addition of 3% (w/w) of technical CNSL derivatives, except for alkylated cardanol. The antioxidant effectiveness is higher for the addition of 2% (w/w) of natural CNSL derivatives, except for anacardic acid and pure. Based on kinetic parameters the order of antioxidant activity for technical CNSL derivative was: CNSL >> cardanol ≅ hydrogenated and alkylated cardanol >> hydrogenated cardanol. For natural CNSL components the order was: cardol > cardanol >> CNSL >> Anacardic acid. Thermogravimetric analyses reveals that the addition of LCC derivatives provide stabilization of PIS in atmosphere of nitrogen, as well as in synthetic air. The commercial antioxidants: IPPD (N-isopropyl-N-phenil-p-phenilene-diamine), DPPD (N,N’-phenil-p- phenilene-diamine), Banox H (2,2,4-trimethyl-1,2-dihidroquinoline-polimerizade) and Banox S (phenol styrened) presented a quite superior activity, except for BHT (2,6-di-terc-buthyl-4-methyl-phenol. Among β-naftol derivatives, AO-3 (1,6-diamine-β-naftol) presented a similar antioxidant activity to IPPD, although with smaller values of the apparent rate constants. On the other hand, the derivatives AO-1 (6-N-ethyl, N-ethylamine-β-naftol) and AO-2 (6-N-ethyl,N-diethylamine-β-naftol) presented a quite superior antioxidant activity when compared to LCC derivatives, but inferior to AO-3.